Meeting Maternal and Reproductive Health Needs in a Post-Disaster Setting: A Qualitative Case Study From Indonesia. (July 2021) - Sajow, Hely Stenly; Winnington, Rhona; Water, Tineke; Holroyd, Eleanor
Meeting and planning for maternal and reproductive health (MRH) needs during post-disaster scenarios is paramount, however, not without considerable challenges. This study was aimed at understanding the provision of MRH services in Siosar, a relocation site for a population displaced by the volcanic eruption in 2013 of Mount Sinabung, Indonesia. A qualitative case study approach was used, and data were collected through focus group discussions and individual interviews with women of reproductive age, community leaders, health personnel, and policymakers. The findings show that while considerable efforts were made to provide MRH services, these were described as "unfinished, " due to challenges such as changes to funding, inadequate provision of supplies and health personnel, and geographical location. Recommendations are that health and other sectors design a relocation site that counts physical, psychological, and social needs of a community and policymakers integrate humanitarian and development plans that include MRH services into World Health Organization's Building Blocks of Health System.